Peran Muhammad bin Salman terhadap Perubahan Pilar Kenegaraan Arab Saudi - Panji Haryadi (Jurnal ICMES, 2018)
Saudi Arabia has four pillars of the state, namely: Saud Family, Wahhabism, Oil, and Relationship with the United States. In 2017, Muhammad bin Salman (MbS) was appointed the crown prince by his father, Salman bin Abdulazis. Throughout the history of Saudi Arabia this has never happened, usually the crown prince is the brother of the ruling king. Another historical event is MbS took steps to change the three pillars. Changing pillars is a very high risk action, if it fails, the worst consequence is the collapse of the state.